STRATEGI PEMASARAN DIGITAL WISATA DAKWAH OKURA - Aifah Dwi Lestari; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to determine the digital marketing strategy of Wisata Dakwah Okura. This research uses qualitative methods which are able to explain phenomena through data collection through observation, interviews and documentation. Every data obtained by the author is then collected, processed and clearly explained using language that is easy to understand. Data collection techniques by means of in-depth interviews and the author directly went to a tourist destination to observe the place (observation), then retrieve data in form of author's documentation. This research uses a descriptive approach where this research explains in detail about the Digital Marketing Strategy of Wisata Dakwah Okura.Based on the results of research that has been done, The Digital Marketing Strategy of Wisata Dakwah Okura uses a marketing mix strategy with 4P and uses STP Theory to identify and classify consumers / tourists so as to create a product image to tourists and be able to compete well. Then analyze the SWOT to determine the strengths and opportunities of Wisata Dakwah Okura to overcome the weaknesses and threats faced by the management of Wisata Dakwah Okura. By creating a good and right marketing strategies and utilizing Digital Technology (Social Media) such as Instagram and Youtube, this is expected to be able to market and promote Wisata Dakwah Okura widely and be able to benefit from the many tourists who are interested and come to visit Wisata Dakwah Okura.Keywords: Digital Marketing Strategy, Marketing Mix, STP Theory, SWOT Analysis